Mobile-Based Technology for the Management of Chronic Diseases in the Elderly: A Feasibility Study - Shagerdi, Ghazal; Ayatollahi, Haleh; Oskouie, Fatemeh (Current Aging Science, 2019)
Introduction: Population aging and related issues are among the most important challenges in different countries. It seems that the use of remote technology can provide the elderly with better healthcare services and can help them to manage chronic diseases. This research aimed to investigate the experts' views about the feasibility of using mobile-based technology to manage chronic diseases in the elderly. Methods: This was a survey study which was completed in 2018. The participants were the faculty members of the department of geriatrics across the country (n=33). In order to collect data, two questionnaires were used. The first questionnaire contained questions related to the five dimensions of a feasibility study and the second questionnaire consisted of five open questions about the opportunities, threats, strengths and weaknesses of using mobile-based technology in chronic disease management. The qualitative data were analyzed by using content analysis method and the quantitative data were analyzed by using descriptive statistics. Results: From the participants’ perspectives, it was feasible to use mobile-based technology in chronic disease management for elderly people. The mean values for five feasibility dimensions were as follows: ethico-legal dimension (4.09±1.01), scheduling dimension (3.70±1.03), economic dimension (3.47±1.04), operational dimension (3.42±1.12) and technical dimension (3.07±1.27). While such a technology can help increasing the accessibility of healthcare services, raising health literacy, and saving time and costs, the main threats, namely; the misinterpretation of information and the possibility of breeching confidentiality should not be underestimated. Conclusion: The results showed that mHealth and remote medical technologies can be used for chronic disease management among elderly people. However, these technologies have some strengths and weaknesses. In order to succeed in the development and implementation of these projects, it is essential to consider probable threats and weaknesses before implementing the applications.
Keywords: chronic disease management